Analysis and control of improved power quality single‐phase split voltage cascaded converter feeding three‐phase OEIM drive. Issue 8 (4th April 2017) - Kumar, Amritesh; Verma, Vishal
Abstract : The use of single phase induction motor (IM) in fuel dispensing units despite its poor efficiency and torque oscillations causing erroneous dispensing etc. is overdue for replacement with 3 phase IM, drives based on single phase AC‐DC‐AC conversion. But conventional 3 phase IM drive requires high Voltage DC tank capacitor requiring regular replacement due to short life cycle and failure on account of high induced voltage during sudden supply or loads disconnection. This paper presents a new cascaded converter active rectifier (CCAR) unit for splitting single phase to 3 phase to cater variable speed constant v/f controlled open end winding induction motor (OEIM) fuel pump drive. The proposed configuration has an advantage in terms of reduced voltage stress across each split capacitor, reduced leakage current, and distributed voltage stress during sudden supply or load disconnection. A detailed stability analysis is presented in the d ‐ q frame for the control design to access the feasibility of drive operation. The embedded control forces balanced drive operation amidst uneven losses across the H‐bridges and /or unbalanced motor loading effect during transients or intermittent operation. The effectiveness of proposed control algorithm is validated both by simulation and experimentation on the developed same scale hardware prototype.